Using Artificial Intelligence in HRM Processes: An Introduction to Quantitative Research - Bozena E. MATUSIAK (Communications of International Proceedings, 2025)
Human Resource (HR) professionals, particularly within high-technology enterprises, are increasingly integrating artificial intelligence (AI)-powered tools, such as ChatGPT and similar systems, into key HR functions, including recruitment, talent acquisition, employee development, training, and other strategic areas. This study addresses the research gap and evaluates the level of awareness and acceptance of AI-driven HR solutions within organizations in Poland and evaluates their effectiveness in streamlining HR processes. To achieve this objective, a preliminary literature review was conducted, followed by a quantitative survey involving a randomly selected sample of n = 600 respondents from high-technology companies. The study analysed descriptive statistics on the level of trust and awareness of AI capabilities and the efficiency of AI-assisted HR applications, with a particular focus on recruitment and employee development. Furthermore, this paper introduces a conceptual research model for next research  and presents a preliminary analysis of the survey findings. Employees in Polish companies demonstrate moderate awareness and high confidence in utilizing AI-driven tools for specific HR functions, such as recruitment, talent acquisition, and professional development processes.
Keywords: Artificial intelligence; HR processes management; awareness; efficiency